"A Bull in Our China Shop:" Japanese Imports and the American Pottery Industry. (9th March 2018) - VINCENT, STEPHANIE
Abstract : From its beginning, the American pottery industry had to contend with the presence of imports. At first, manufacturers coped by promoting their own products and striving to improve design and quality. However, when Japan began importing china in greater quantities, American potters faced a challenge unlike any before. Initial attempts to attack imports outright through boycotts met with limited success through World War II. Following the peace, Cold War economic policy designed to reintroduce Japan to the global market led to another round of increasing importation. U.S. potters decried the poor quality and low wages connected to Japanese china, yet could not agree on a strategy to overcome the growing number of imports. Some filed lawsuits over copied designs while others hoped to contract with the Japanese to import on their own terms. The failure of these manufacturers to unify in response to Japan proved one of the most damaging blows to this small industry.